2010
DOI: 10.1242/jcs.066514
|View full text |Cite
|
Sign up to set email alerts
|

p38γ regulates interaction of nuclear PSF and RNA with the tumour-suppressor hDlg in response to osmotic shock

Abstract: Activation of p38γ modulates the integrity of the complex formed by the human discs large protein (hDlg) with cytoskeletal proteins, which is important for cell adaptation to changes in environmental osmolarity. Here we report that, in response to hyperosmotic stress, p38γ also regulates formation of complexes between hDlg and the nuclear protein polypyrimidine tract-binding protein-associated-splicing factor (PSF). Following osmotic shock, p38γ in the cell nucleus increases its association with nuclear hDlg, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 32 publications
1
25
0
Order By: Relevance
“…One possibility is modulation of the affinity of PSF for its targets. For example, interaction of the scaffold protein hDlg with its kinase p38γ decreases hDlg/PSF association . Conversely, the addition of poly(ADP‐ribose) (PAR) to proteins (PARylation) increases the binding affinity of NONO, and perhaps PSF, through interaction of PAR with RRM1 .…”
Section: Regulation Of Psfmentioning
confidence: 99%
See 1 more Smart Citation
“…One possibility is modulation of the affinity of PSF for its targets. For example, interaction of the scaffold protein hDlg with its kinase p38γ decreases hDlg/PSF association . Conversely, the addition of poly(ADP‐ribose) (PAR) to proteins (PARylation) increases the binding affinity of NONO, and perhaps PSF, through interaction of PAR with RRM1 .…”
Section: Regulation Of Psfmentioning
confidence: 99%
“…For example, interaction of the scaffold protein hDlg with its kinase p38 decreases hDlg/PSF association. 107 Conversely, the addition of poly(ADP-ribose) (PAR) to proteins (PARylation) increases the binding affinity of NONO, and perhaps PSF, through interaction of PAR with RRM1. 108 PARylation of histones is often a mark for sites of DNA damage and has been linked to recruitment of PSF and p54nrb/NONO for DNA repair.…”
Section: Psf-co-associated Proteinsmentioning
confidence: 99%
“…Previous studies showed that p38␥ is both cytoplasmic and nuclear, whereas its phosphorylated form is predominantly localized in the nucleus (33)(34)(35). Because phosphorylated p38␥ protein is up-regulated in K-Ras mutant cells (15), we examined whether K-Ras mutation triggers p38␥ nuclear translocation, thus increasing its interaction with c-Jun.…”
Section: P38␥ Stimulates Egfr Transcription Through C-jun-mediated Bimentioning
confidence: 99%
“…In yeast, it has been reported that, in response to osmotic or heat stress, Hog1 and Mpk1, respectively, phosphorylate components of the nuclear pore complex to increase the export efficiency of stress-responsive mRNAs [72,73]. Similarly, in mammals, both p38 and ERK pathways regulate RNA-binding proteins such as eIF4E or hDl1 that facilitate mRNA export [74,75]. In the event of stress, the export of the newly transcribed mRNAs is prioritized to maximize the transcriptional response.…”
Section: Mrna Exportmentioning
confidence: 99%